Il territorio della neoruralità nell’area milanese/lombarda: mappatura e strumentazione informatica interattiva delle esperienze - Iero, Alessandra (Scienze del Territorio, 2018)
Starting from previous new ruralism experiences, OsTeMi (Osservatorio Territorialista Milanese), has activated, since 2016, an interaction with others counterparts in the Milan area through meetings and exchanges on web platforms; these interactions led to a first map representing the new ruralism existing in the Lombardy area. The exchanges between ‘know-how’ knowledge and ‘expert’ knowledge is currently a work in progress evolving towards a shared prototype aimed to represent and communicate all the relevant data within the framework of the European tool “INSPIRE”.